A framework for the management of the pediatric airway. Issue 10 (2nd September 2019) - Engelhardt, Thomas; Fiadjoe, John E.; Weiss, Markus; Baker, Paul; Bew, Stephanie; Echeverry Marín, Piedad; von Ungern‐Sternberg, Britta S
Summary: Critical airway incidents in children are a frequent problem in pediatric anesthesia and remain a significant cause of morbidity and mortality. Young children are at particular risk in the perioperative period. Delayed management of airway obstruction can quickly lead to serious complications due to the short apnea tolerance in children. A simple, time critical, and pediatric‐specific airway management approach combined with dedicated teaching, training, and frequent practice will help to reduce airway‐related pediatric morbidity and mortality. There is currently no pediatric‐specific universal framework available to guide practice. Current algorithms are modifications of adult approaches which are often inappropriate because of differences in age‐related anatomy, physiology, and neurodevelopment. A universal and pragmatic approach is required to achieve acceptance across diverse pediatric clinicians, societies, and groups. Such a framework will also help to establish minimum standards for pediatric airway equipment, personnel, and medications whenever pediatric airway management is required.